Percolating Risk Factors for Cardiovascular Diseases in Rural North India - Mishra, Abhishek; Bano, Tanveer; Jain , Seema; Singh, Ganesh; Gautam, Neelam; Chaudhary, Parul (Indian Journal of Community Health, 2024)
Background: World has seen a tremendous epidemiological transition in disease patterns from communicable to non-communicable diseases (NCDs). Currently cardiovascular diseases are a major cause of disability and premature deaths globally. Objective: (1) To know prevalence of various risk factors of cardiovascular diseases in the rural area of Meerut. (2) To find out the association of sociodemographic factors with hypertension. Settings and design: A cross-sectional study was conducted in Machchra village. Methods: The study was conducted among 315 study participants over time period of one year in which all the adults aged >30 years above residing in the ward of study area were included. Sampling technique used was systematic random sampling. Results: The prevalence of hypertension, diabetes and hypercholesterolemia was found to be 30.2%, 22.2% and 15.2% respectively. The prevalence of pre-obese and obese were 14.3% and 7.0% respectively. The maximum prevalence of hypertension was seen in the age group of 70 years (66.7%), in females (30.6%), SES as class IV (36.5%), secondary school completed population (42.9%) and among homemakers (40.9%). The prevalence of hypertension was found to be statistically significant in relation to age, educational status and occupation. Conclusion: In our study the prevalence of hypertension was found to be 30.2% (in males 29.6% while in females 30.6%).